Recurrent Hydatiform Mole: Report of A Case with Fourth Recurrence - Karataylı, Rengin; Gezginç, Kazım; Gök, Dilay; Acar, Ali (Gynecology Obstetrics & Reproductive Medicine, 2012)
In this report, it is objected to demonstrate 4th recurrence of molar pregnancy in a patient with a past history of 3 suction curettages for 2 complete and 1 partial moles. A 31-year-old woman was referred to our hospital with diagnosis of mole. There was no history of consanguinity. The mother of the patient had history of molar pregnancy and both sisters had primary infertility and IVF failures. Karyotype analysis of the patient and her husband was normal. The calculated serum β-hCG level was 188000IU/ml and she had an endometrial thickness of 40mm with a crumb like image. Thyroid function tests were normal. Suction curettage was performed and histopathological examination revealed complete HM. The patient is still being followed up with serial serum β-hCG levels. Families who have recurrent molar pregnancies should be informed about that subsequent pregnancies are at increased risk of having molar conception.